PENGARUH COACH LEADERSHIP TERHADAP MOTIVASI DAN ACHIEVEMENT ATLET BOLA BASKET UNIVERSITAS SWASTA DI SURABAYA - Gunawan, Evelin Melianawati; Setiobudi, Auditia (Universitas Ciputra Surabaya, 2023)
This research is quantitative research. The purpose of this research is to find out the effect of coach leadership on motivation and also on achievement of students who are joined in basketball team of private Universities in Surabaya. Data analysis method in this research uses multiple linear regression analysis by using SPSS help. The total sample in this research is 83 student respondents who are joined in basketball team of the private Universities in Surabaya. In this research, the data is collected by using questionnaires that are given to students who are joined in basketball team of private Universities in Surabaya with the limitation of basketball players who have ever participated in student competition team with a period approximately less than a year. Based on the result of the research that has been don , therefore it can be concluded that the coach leadership variable affects motivation variable with positive regression coefficient of 0.399. It is proved with significant value that is obtained as 0.000 (<0.05) and T calculation > T table (6.302> 1.989). In addition, coach leadership variable affects on achievement variable with positive regression coefficient of 0.199. This result is proved with significant value that is obtained as 0.000 (<0.05) and T calculation > T table (8,095> 1,989). The final conclusion that can be outlined based on the result of research that has been carried out shows that motivation variable affects on achievement variable with positive regression coefficient of 0.343. The effect of these two variables are proved with significant value that is obtained as 0.000 (<0.05) and T calculation is > T table (12.051> 1.989).